STUDY OF PROPERTIES CDS NANOCRYSTALLINE THIN FILM AS A PHOTODETECTOR - Abdulelah , Haider; Shabeeb , Ghufran Mohammad (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
It has been discussing the use of cadmium sulfide (CdS) as a material for photodetectors. CdS is a direct bandgap II-VI semiconductor with desirable properties for photodetectors, including high sensitivity, fast response time, and wide spectral range from ultraviolet to near-infrared. X-ray diffraction analysis confirmed the cubic crystal structure of the porous CdS thin film. Scanning electron microscopy revealed a porous morphology with macropores ranging from 200-300 nm in size. The performance of the porous CdS photodetector was evaluated. Under visible light illumination, the device generated a photocurrent of 16 nA, with response times of around 5 seconds for both the rising and falling edges of the light-induced current